The Aplication of Ripening Stimulant at Barangan Banana (Musa paradisiacal L) with Modified Atmosphere Packaging - Kajima Juniaman Siahaan; Elisa Julianti; Ridwansyah - (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The research has been carried out in April 2012 at the Laboratory of Food Chemistry Analysys Faculty of Agriculture University of Sumatera Utara.  The aim of this research was to investigate whether ripening processes in barangan banana fruits which are delayed by modified atmosphere packaging for 2 weeks, could be initiated with ripening stimulants treatment and produce good quality of ripe fruit. The type of modified atmosphere packaging consisted active modified atmosphere packaging and stored in 150C and in ambient temperature, passive modified atmosphere packaging and stored in 150C and in ambient temperature. The samples were stored for 15 days and after termination of storage, they were shifted to ambient temperature and air normal of atmosphere, tretated with ripening stimulant for 2 days.  The ripening stimulant used consists of ethepon 250 ppm, ethylene gas 250 ppm, asethylene gas 250 ppm, and calsium carbide 0,5%. The results showed that the method of packaging and the kind of ripening stimulant had a significant effect on the quality of ripe barangan banana fruit. The best result was obtained in a combination of active modified atmosphere packaging that stored in 150C for 15 days followed by ethylene gas treatment with the concentration of 250 ppm. In this treatment the level of moisture content was 48,161%, level vitamin C content was 22,568 mg/100g, total acid was 22,568%, total sugar was 13,328%, total soluble solid (TSS) of 12,0oBrix, hardness of 3,859 kgf, weight reduction was 1,964%, ratio of pulp and skin was 1,332, color score was 6,000 and acceptable organoleptic value.